Milk and cheese - Hewitt, Sally, 1949- (London : Wayland, 2007)
Explores the nutrients, preparation, and storage of dairy products such as milk, cheese, and yogurt, and includes a food chart.
Includes index.
2.2
K-3.
K-3
Keywords: Cheesemaking -- Juvenile literature; Dairy processing -- Juvenile literature; Milk -- Juvenile literature; Cheese -- Fiction; Cheese -- Fiction; Milk; Milk